PENANGANAN GURU BIMBINGAN DAN KONSELING DALAM MENGATASI MASALAH SISWA DI SMK BHAKTI BANGSA BANJARBARU - Maisaroh, Maisaroh; Auliah, Nurul (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2018)
Adolescence is a time of changing life dependence on others. Teenagers begin to determine their way of life. During undergoing the formation of maturity in attitude, various mental changes occur, maybe even shock. Such conditions are strongly influenced by the environment in which he lives. On the other hand teenagers often do not have a place to complain to solve the problems they face. So that as a teenager escape often falls, such as smoking, drinking, narcotics, free sex, and other criminal acts.In this study, researchers used qualitative research methods with descriptive types. The source of the data in this study is the Guidance and Counseling teacher and some problematic students who are known through the interview process with data sources, namely the Guidance and Counseling teacher.The results of this study indicate that the Handling of Efforts carried out by the Guidance and Counseling teacher in overcoming the problems of students in Banjarbaru National Vocational High School is to find the background of the problems faced by students, so the BK teacher and the school are able to solve the problem by looking at the factors or causes why students experience or get the problem. And to give a deterrent effect to students who are in trouble, the BK teacher will give mild or severe sanctions depending on the problems made by students.Efforts that have been made to overcome the problem of students with procedures in the process of handling the problem is to find the cause of the problem and then provide direction and guidance advice so that students are able to understand and the same error does not happen again. And in the process of handling it can not be separated from cooperation with schools such as homerooms, vice principals of student affairs, and the principal. Keywords: The Role of Guidance and Counseling Teachers,